NIR-II-excited off-on-off fluorescent nanoprobes for sensitive molecular imaging in vivo - Yufu Tang; Yuanyuan Li; Chunxu He; Zhen Wang; Wei Huang; Quli Fan; Bin Liu (Nature Communications)
Abstract Strong background interference signals from normal tissues have significantly compromised the sensitive fluorescence imaging of early disease tissues with exogenous probes in vivo, particularly for sensitive fluorescence imaging of early liver disease due to the liver’s significant uptake and accumulation of exogenous nanoprobes, coupled with high tissue autofluorescence and deep tissue depth. As a proof-of-concept study, we herein report a near-infrared-II (NIR-II, 1.0-1.7 μm) light-excited “off-on-off” NIR-II fluorescent probe (NDP). It has near-ideal zero initial probe fluorescence but can turn on its NIR-II fluorescence in liver cancer tissues and then turn off the fluorescence again upon migration from cancer to normal tissues to minimize background interference. Due to its low background, a blind study employing our probes could identify female mice with orthotopic liver tumors with 100% accuracy from mixed subjects of healthy and tumor mice, and implemented sensitive locating of early orthotopic liver tumors with sizes as small as 4 mm. Our NIR-II-excited “off-on-off” probe design concept not only provides a promising molecular design guideline for sensitive imaging of early liver cancer but also could be generalized for sensitive imaging of other early disease lesions.